Factors Affecting Parental Intent to Vaccinate Against COVID-19 in the United States - Duncan , Leah; Baalmann, David; Loo-Gross, Colleen; Regehr, Jared; Martin, Francis; Mcghie, Ronan; McKaughan, Kevin; Ofei-Dodoo, Samuel (Kansas Journal of Medicine, 2024)
Introduction. The topic of childhood vaccinations has become increasingly contentious, sparking debate and challenging decisions for parents, study aimed to explore the factors influencing COVID-19 vaccination plans for parents of unvaccinated children and identify the most common reasons for not vaccinating children against COVID-19 in the United States. Methods. Authors analyzed data from Phase 3.7, Week 53 of the United States Census Bureau’s Household Pulse Survey (N = 68,504), collected from January 4 to January 16, 2023. Standard descriptive statistics and adjusted odds ratio (aOR) were used to analyze the data. Results. The top three reasons given for vaccine hesitancy were concerns about side effects, not trusting the vaccine, and children in the household not members of a high-risk group. Nearly 87% (n = 59,363) of respondents reported having received a COVID-19 vaccination, these respondents were more likely to vaccinate their children in all three age ranges studied. Participants with higher levels of education (bachelor’s degree or higher) were also more likely to vaccinate their children against COVID-19. (≤ associate degree; aOR = 5.79; 95% CI, 5.43 to 6.17; P <.001). Conclusions. Insights from this study provide a deeper understanding of parents’ decision-making processes regarding COVID-19 vaccination for their children. Educational programs tailored to the factors identified in this study could potentially enhance vaccine acceptance among children and adolescents.